2014
DOI: 10.1371/journal.pone.0112449
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution, Gender- and Genotype-Dependent Expression of Autophagy-Related Genes in Avian Species

Abstract: As a result of the genetic selection of broiler (meat-type breeders) chickens for enhanced growth rate and lower feed conversion ratio, it has become necessary to restrict feed intake. When broilers are fed ad libitum, they would become obese and suffer from several health-related problems. A vital adaptation to starvation is autophagy, a self-eating mechanism for recycling cellular constituents. The autophagy pathway has witnessed dramatic growth in the last few years and extensively studied in yeast and mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…Potential reasons or mechanism for this differential signaling during disuse have yet to be elucidated. While females tend to have less ubiquitinproteasome activity compared to males, females tend to have greater autophagy-related protein degradation compared to males [81,82]. Current literature suggests greater protein content of autophagy regulators of autophagy initiation and resolution compared to males [81,82], overall suggesting that males and females may preferentially favor different protein catabolic pathways.…”
Section: Sex Difference In Anabolic and Catabolic Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Potential reasons or mechanism for this differential signaling during disuse have yet to be elucidated. While females tend to have less ubiquitinproteasome activity compared to males, females tend to have greater autophagy-related protein degradation compared to males [81,82]. Current literature suggests greater protein content of autophagy regulators of autophagy initiation and resolution compared to males [81,82], overall suggesting that males and females may preferentially favor different protein catabolic pathways.…”
Section: Sex Difference In Anabolic and Catabolic Factorsmentioning
confidence: 98%
“…Females tend to have less satellite cells [60,61], which may be partially mediated by testosterone-activation of ARs on the satellite cells [64][65][66]. Females also tend to have less basal ubiquitin-proteasome activity and greater autophagy activity compared to males [79][80][81][82]. Finally, females appear to have differential regulation of myostatin activity and subsequent alterations to muscle physiology [49,98].…”
Section: Sex Difference In Anabolic and Catabolic Factorsmentioning
confidence: 99%
“…Interestingly, we found that the expression of autophagy-related genes is tissueand gender-dependent. 47 For instance, it was found that hypothalamic Beclin1, UVRAC, Atg9a, Atg13, Atg4b, Atg7 and Atg5 mRNA levels were significantly higher in female compared to male chickens suggesting that hypothalamic autophagy might be involved in the regulation of feed intake. Recently, Kaushik and colleagues showed that autophagy regulates lipid metabolism within hypothalamic neurons which in turn modulate neuropeptide levels that control feed intake and energy homeostasis.…”
mentioning
confidence: 99%
“…47 These genes are ubiquitously expressed and showed high similarity with their mammalian orthologs indicating that autophagy is a conserved mechanism in different species. Interestingly, we found that the expression of autophagy-related genes is tissueand gender-dependent.…”
mentioning
confidence: 99%
See 1 more Smart Citation